Romano Pisciotti v Bundesrepublik Deutschland: Increased Risk of Extradition for EU Citizens after Involvement in US Cartels. (4th April 2019) - Stange, Beatrice
Abstract: Case C-191/16 – Romano Pisciotti v Bundesrepublik Deutschland, 10 April 2018 Germany is not obliged to grant its constitutional prohibition of extradition to all Union citizens.